Protein-bound uremic toxins as therapeutic targets for cardiovascular, kidney, and metabolic disorders - Zhang, Shihan; Tang, Shasha; Liu, Yalei; Xue, Binghua; Xie, Qinyuan; Zhao, Lingyun; Yuan, Huijuan (Frontiers in Endocrinology, 2025)
Cardiovascular-kidney-metabolic (CKM) syndrome is a systemic clinical condition characterized by pathological and physiological interactions among metabolic abnormalities, chronic kidney disease, and cardiovascular diseases, leading to multi-organ dysfunction and a higher incidence of cardiovascular endpoints. Traditional approaches to managing CKM syndrome risk are inadequate in these patients, necessitating strategies targeting specific CKM syndrome risk factors. Increasing evidence suggests that addressing uremic toxins and/or pathways induced by uremic toxins may reduce CKM syndrome risk and treat the disease. This review explores the interactions among heart, kidney, and metabolic pathways in the context of uremic toxins and underscores the significant role of uremic toxins as potential therapeutic targets in the pathophysiology of these diseases. Strategies aimed at regulating these uremic toxins offer potential avenues for reversing and managing CKM syndrome, providing new insights for its clinical diagnosis and treatment.